Improved load frequency control in dual-area hybrid renewable power systems utilizing PID controllers optimized by the salp swarm algorithm - Sreenivasan, Pushpa; Dhandapani, Lakshmi; Natarajan, Shanthi; Adaikalam, Arul Doss; Sivakumar, Amudhapriya (Institute of Advanced Engineering and Science, 2024)
In this study, we utilize the salp swarm algorithm (SSA) to optimize proportional integral derivative (PID) controller gains for load frequency control (LFC) in a multi-area hybrid renewable nonlinear power system. Incorporating generation rate constraints and dead-bands into the governor model, we examine system nonlinearities. Performance evaluation employs both single- and multi-objective functions, with actual sun irradiation data validating SSA-PID controllers' efficacy in managing renewable energy source uncertainties. Comparing with alternative optimization techniques across various operational scenarios reveals the SSA-PID controller's 15% improvement in dynamic response time. The findings suggest SSA enhances LFC dynamic response in hybrid renewable power systems, with potential generalizability. These results underscore SSA's utility in addressing system complexities, offering implications for improved stability and efficiency across renewable energy integration scenarios.